(untitled) (Prostor, 2023)
The “Boska” Department Store is a large building at the historical core of Banja Luka (Bosnia and Herzegovina). Its distinctive volume dominates the main city square, and it serves as one of the city symbols. It was built in 1978 as one of the large department stores that characterised Yugoslav cities. However, “Boska” and the less famous neighbouring The Worker’s Solidarity House are fragments of an extensive revitalisation project of the city centre and a new imagined megaform. This paper will portray the winning competition design project “Grad” (“City”) from 1973 by a team of eminent Yugoslav architects who envisioned a new urban landscape in Banja Luka’s centre that never materialised. The paper will interpret its design principles in the context of the period’s local and international architectural culture that pursued the new spatial synthesis of fixed and transient space, architecture and the city. Qualitative research is based on analysing the design project “Grad”, relevant journal articles from the period, and a recent interview with one of the authors.